ARE PRICE FAIRNESS AND PRODUCT QUALITY IMPORTANT TO CONSUMERS OF ASIAN STREET FOOD? - Widyarini, Lydia Ari; Sanjaya, Jordy Kusuma; Agrippina, Yulika Rosita (Distribusi - Journal of Management and Business, 2025)
The food and beverage industry in Indonesia continues to demonstrate robust revenue growth, particularly within the Asian street food segment especially Mixue, tea and ice cream an area that remains relatively underexplored in empirical research. This study aims to examine the effect of price fairness and product quality on repurchase intention, with perceived value and customer satisfaction serving as mediating variables. Data were collected using a purposive sampling method through an online questionnaire distributed via Google Forms, and further disseminated using a snowball sampling technique to increase respondent reach. A total of 192 valid responses were analyzed using Structural Equation Modeling (SEM) with SmartPLS 3.0. The findings reveal that both price fairness and product quality have a positive and significant impact on perceived value and repurchase intention. Furthermore, perceived value significantly influences customer satisfaction, which in turn also has a positive and significant effect on repurchase intention. These results underscore the critical role of perceived fairness and quality in shaping consumer behavior in the competitive street food market. The study provides valuable insights for food service operators and marketers seeking to enhance customer loyalty through pricing strategies and product excellence.